Regulating liquid film disturbance via disk configurations for photochemical process intensification in a spinning disk reactor. (5th June 2023) - Li, Zhi-Hao; Li, Yan-Bin; Zhu, Yu-Gan; Xu, Ying-Chun; Sun, Bao-Chang; Zou, Hai-Kui; Chu, Guang-Wen
Graphical abstract: Highlights: SDR with different disk configurations were designed to regulate liquid film disturbance. Turbulent kinetic energy and liquid streamline of designed SDRs were investigated numerically. Chemical actinometry experiments were performed to verify photochemical process intensification. Photochemical reactions was intensified efficiently by the SDR with different disk configurations. Abstract: Spinning disk reactor (SDR) has been widely applied in photochemistry based on its thin film formation. Regulating flow disturbance inside SDRs is a potential approach to intensify photochemical processes by promoting the uniform light explore. In this work, various disk configurations were developed to regulate the liquid film disturbance in an SDR for photochemical process intensification. Cylindrical spoiler (CS) or elliptic-cylindrical spoiler (ES) arrays were 3D printed on the spinning disk surface. Liquid film disturbance characteristics including turbulent kinetic energy and liquid streamlines was analyzed via numerical simulations. Simulation results indicated that the SDR with ES-0° (the major axis is aligned with the radial direction of the disk) generated the highest average turbulent kinetic energy ( k m ) in the film-propagation direction and the most violent fluctuation of liquid streamlines in the light-irradiation direction. Photon absorption rate ( P a, λ ), a crucial parameter of photochemical reactions, was evaluated experimentally to verify the photochemical process intensification in the SDR with varied disk configurations. Compared with the conventional SDR with smooth disk, the SDR with ES-0° enhanced the k m and had the superior P a, λ, which was increased from 2.1 × 10 -4 m 2 /s 2 to 3.8 × 10 -3 m 2 /s 2 and from 1.77 × 10 -4 mol/min to 2.04 × 10 -4 mol/min under optimum operating conditions, respectively.